Exploration of predictive biomarkers for postoperative recurrence of stage II/III colorectal cancer using genomic sequencing. (28th March 2022) - Kishigami, Fumishi; Tanaka, Yosuke; Yamamoto, Yoko; Ueno, Toshihide; Kojima, Shinya; Sato, Kazuhito; Inoue, Satoshi; Sugaya, Saori; Ishihara, Soichiro; Mano, Hiroyuki; Kawazu, Masahito
Abstract: Postoperative recurrence of colorectal cancer (CRC) eventually leads to therapeutic failure; therefore, treatment strategies based on accurate prediction of recurrence are urgently required. To identify biomarkers that can predict treatment outcomes, we compared the mutational profiles of surgically resected specimens from patients with recurrent cancer with those from patients with non‐recurrent cancer. Target sequencing, whole‐exome sequencing (WES), or whole‐genome sequencing (WGS) was performed on 89 and 58 tumors from recurrent and non‐recurrent cases, respectively. WGS revealed the driver mutations that were not detected with target sequencing or WES, including the structural variations affecting ZFP36L2 . Loss of function of ZFP36L2 was frequently observed in primary tumors from recurrent cases. Furthermore, the recurrence‐free survival of patients with loss of function of ZFP36L2 was significantly shorter relative to patients with no loss of ZFP36L2 function. In summary, the study demonstrated that detailed genomic analysis could help improve precision medicine for CRC. Abstract : Loss of function of ZFP36L2 was frequently observed in recurrent colorectal cancers. Furthermore, the recurrence‐free survival of colorectal cancer patients with loss of function of ZFP36L2 was significantly shorter relative to patients with no loss of ZFP36L2 function.